Analysis of Green Product Innovation and Cleaner Production Technology on Business Sustainability and Competitive Advantage in the Beauty Industry in West Java - Hendriana, Tengku Ine; Novitasari, Salwa Aulia; Pahrijal, Rival (West Science Social and Humanities Studies, 2024)
This study examines the impact of Green Product Innovation and Cleaner Production Technology on Business Sustainability and Competitive Advantage in the beauty industry in West Java. As environmental concerns and consumer demand for sustainable products grow, companies are increasingly adopting eco-friendly practices to enhance both their operational sustainability and market position. Using a quantitative research approach, data were collected from 160 beauty firms and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that Green Product Innovation and Cleaner Production Technology positively influence Business Sustainability, which in turn significantly enhances Competitive Advantage. These results underscore the strategic importance of integrating sustainability practices, highlighting their dual role in promoting environmental responsibility and providing a competitive edge. This study contributes to the literature on sustainability in the beauty industry and offers practical insights for industry practitioners aiming to achieve long-term success in a competitive and eco-conscious market.